Coupled-Mode Parabolic Equations for the Modeling of Sound Propagation in a Shallow-Water Waveguide with Weak Elastic Bottom - Sergey Kozitskiy (Journal of Marine Science and Engineering, 2022)
In this work, a mode parabolic equation method with interacting modes accounting for the weak elasticity at the bottom is developed. An important feature of the proposed method is that computations of elastic modes are avoided and that the solution is obtained in the form of expansion over acoustic modes. A numerical technique for solving resulting mode parabolic equations is developed, and the accuracy and efficiency of the resulting solution is validated by a direct comparison against source image solutions in the 3D wedge benchmark problem. Satisfactory agreement of the two solutions is achieved for sufficiently small values of shear wave speed that are typical for soft sediments of the sea bottom. The developed approach may be used for solving 3D problems of sound propagation with the elastic properties of bottom sediments taken into account.